Resensi Buku "Altruism and Beyond: An Economic Analysis of Transfers and Exchanges within Families and Groups". - Evita Hanie Pangaribowo (Populasi, 2009)
Judul: Altruism and Beyond: An Economic Analysis of Transfers and Exchanges within Families and Groups. Pengarang: Oded StarkPenerbit: Cambridge University PressTahun: 1995Tebal: 154 halaman.